(untitled) (Research, Society and Development, 2024)
Objective: to develop a clinical guide for a Federal University Hospital in Rio de Janeiro, based on the identification and scientific analysis of diagnostic methods used to detect osteomyelitis in adult wounds. Methodology: integrative review, whose inclusion criteria were complete articles on the topic, published from 2018 onwards, in Portuguese, Spanish or English. Animal studies, children under 18 years of age, case reports and projects are excluded. The systematic search took place using Health Sciences Descriptors (DeCS) and Medical Subject Heading (MeSH). Results: 470 articles identified, after removing duplicates and evaluation by two researchers, 50 included and analyzed, the majority of which were of American origin (34%) and published by doctors (96%). Regarding diagnostic issues, the most cited clinical signs for predictive assessment were signs of phlogosis (54%) and bone exposure (40%). Laboratory tests - microbiological culture (90%), C-reactive protein (68%) and erythrocyte sedimentation rate (68%) compatible with infectious and inflammatory assessment. Regarding images, radiography led with 70% of screening indications combined with the clinical sign of bone percussion, followed by magnetic resonance imaging (58%). Regarding invasive exams, bone biopsy (82%) appeared as the gold standard. Conclusion: with the articles analyzed, it was not possible to point out a consensus on the hierarchy of diagnostic processes, but it was possible to highlight clinical, laboratory, imaging and surgical recommendations that can help nurses in clinical practice to make an early diagnosis, forwarding them to other professionals, avoiding the increase in morbidity and mortality from a public health problem.